Detection by radioimmunoassay and enzyme-linked immunosorbent assay of coronavirus antibodies in bovine serum and lacteal secretions. - Rodak, L (1982)
The sensitivity of a radioimmunoassay (RIA), an enzyme-linked immunosorbent assay (ELISA), and a serum neutralization assay (SN) for detecting antibodies to bovine coronavirus in serum and colostrum were compared. Although there proved to be a good correlation among all three assays (r = 0.915 and 0.964 for RIA with SN and ELISA, respectively), RIA and ELISA proved to be at least 10 times more sensitive than neutralization tests. By using these techniques, it was possible to detect a time-dependent decrease in antibody levels in bovine colostrum after parturition. Using ELISA, we demonstrated that 12 of 12 herds in Saskatchewan, and 109 of 110 animals tested, and antibody to bovine coronavirus. There was no elevated antibody response in serum or lacteal secretions of cows vaccinated once or twice with a commercially available modified live rota-coronavirus vaccine. In addition to being more sensitive than SN, ELISA and RIA proved to have other advantages for measuring antibody levels to bovine coronavirus and therefore warrant wider use as tools in diagnostic virology.